PENGARUH MODEL EXAMPLE NON EXAMPLE TERHADAP KEMAMPUAN BERFIKIR RASIONAL SISWA - Eka Rahmawati; Pramudiyanti Pramudiyanti; Rini Rita T Marpaung (Universitas Lampung, 2014)
The aim of this study was to know the influence of Example Non Example learning model to the student’s ability to think rationally. This research was an experimental study with pretest-posttest non equivalent group design. The sample of this research were class VIIa and VIIb selected by using cluster random sampling. The research data consisted of quantitative and qualitative data. The quantitative data obtained from the average value of test were analyzed by using t-test or U test. The qualitative data obtained from the observation sheet of learning activities and student feedback questionnaires were analyzed descriptively. The results demonstrate that the ability to think rationally students has increased by an average of N-gain was 73.15. Student learning activities also increased by an average was 83.08. Thus , the use of Example Non Example learning model was influenced significantly in improving the students’s ability to think rationally and learning activities in the pollution and environmental damage subject matter. Penelitian ini bertujuan mengetahui pengaruh model pembelajaran Example Non Example terhadap kemampuan berfikir rasional siswa. Penelitian ini merupakan studi eksperimen dengan desain pretes-postes non ekuivalen. Sampel penelitian adalah siswa kelas VIIa dan VIIb yang dipilih secara cluster random sampling. Data penelitian terdiri dari data kuantitatif dan kualitatif. Data kuantitatif diperoleh dari rata-rata nilai tes yang dianalisis menggunakan uji-t atau uji U. Data kualitatif diperoleh dari lembar observasi aktivitas belajar dan angket tanggapan siswa yang dianalisis secara deskriptif. Hasil penelitian menunjukkan kemampuan berfikir rasional siswa mengalami peningkatan dengan rata-rata Ngain 73,15. Aktivitas belajar siswa juga mengalami peningkatan dengan rata-rata 83,08. Dengan demikian, penggunaan model pembelajaran Example Non Example berpengaruh signifikan dalam meningkatkan kemampuan berfikir rasional dan aktivitas belajar siswa pada materi pokok pencemaran dan kerusakan lingkungan.Kata kunci : aktivitas belajar siswa, example non example, kemampuan berfikir rasional, pencemaran dan kerusakan lingkungan